2019
DOI: 10.1002/cctc.201901466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ordered Mesoporous Alumina Support on the Structural and Catalytic Properties of Mn−Ni/OMA Catalyst for NH3−SCR Performance at Low‐temperature

Abstract: MnÀ Ni oxides supported on ordered mesoporous alumina (OMA) catalysts were applied to the NH 3 À SCR of NO x at lowtemperature compared with MnÀ Ni oxides supported on commercial γ-Al 2 O 3 . The NO x conversion and N 2 selectivity of MnÀ Ni/OMA were superior to the MnÀ Ni/γ-Al 2 O 3 in the temperature window of 90~240°C. BET, XRD, NH 3 À TPD, NO + O 2 À TPD, Pyridine-IR, H 2 À TPR, and XPS were performed to characterized the physicochemical properties of the catalysts. The characterization results manifested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…It can be suggested that the OM‐supported catalysts exhibited more exposed surface hydroxy groups, hence the presence of the bands at 1540 cm −1 . Similar findings were also observed in previous studies [50] …”
Section: Resultssupporting
confidence: 93%
“…It can be suggested that the OM‐supported catalysts exhibited more exposed surface hydroxy groups, hence the presence of the bands at 1540 cm −1 . Similar findings were also observed in previous studies [50] …”
Section: Resultssupporting
confidence: 93%
“…A manganese oxide (MnO x ) SCR catalyst has been widely used for NO x removal because of its low cost, high thermal stability and higher SCR activity than other catalysts at low temperatures (Xu et al 2013). However, as MnO x loading amount increases agglomeration increases and MnO x is not dispersed perfectly on the catalyst surface (Liu et al 2016). Liu et al (2016) found that Mn-Ni/OMA exhibits higher NO x conversion performance than Mn-Ni/γ-Al 2 O 3 in the 90-240°C temperature window.…”
Section: Introductionmentioning
confidence: 99%
“…However, as MnO x loading amount increases agglomeration increases and MnO x is not dispersed perfectly on the catalyst surface (Liu et al 2016). Liu et al (2016) found that Mn-Ni/OMA exhibits higher NO x conversion performance than Mn-Ni/γ-Al 2 O 3 in the 90-240°C temperature window. Guo et al (2019) revealed that Mn-Eu-Fe catalyst with Fe/Mn molar ratio of 1 and calcination temperature of 500°C has the highest SCR activity with 98% NO conversion at 100°C using NH 3 reductant.…”
Section: Introductionmentioning
confidence: 99%
“…A manganese oxide (MnOx) SCR catalyst has been widely used for NOx removal because of its low cost, high thermal stability and higher SCR activity than other catalysts at low temperatures [7]. However, as MnOx loading amount increases agglomeration increases and MnOx is not dispersed perfectly on the catalyst surface [8]. Liu et al [8] found that Mn-Ni/OMA exhibits higher NOx conversion performance than Mn-Ni/γ-Al2O3 in the 90-240 °C temperature window.…”
Section: Introductionmentioning
confidence: 99%
“…However, as MnOx loading amount increases agglomeration increases and MnOx is not dispersed perfectly on the catalyst surface [8]. Liu et al [8] found that Mn-Ni/OMA exhibits higher NOx conversion performance than Mn-Ni/γ-Al2O3 in the 90-240 °C temperature window. Guo et al [9] revealed that Mn-Eu-Fe catalyst with Fe/Mn molar ratio of 1 and calcination temperature of 500 °C has the highest SCR activity with 98% NO conversion at 100 °C using NH3 reductant.…”
Section: Introductionmentioning
confidence: 99%